2008
DOI: 10.1037/0022-0663.100.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between personal goals and classroom goal structures in predicting student outcomes: A multilevel analysis of person-context interactions.

Abstract: This study examined cross-level interactions between personal goals and classroom goal structures, as well as their additive contributions to predicting math achievement, engagement, interest, effort withdrawal, and avoidance coping, using a sample of 3,943 Grade 5 students from 130 classrooms. Results of hierarchical linear modeling showed that classroom performance goal structures exacerbated (a) the negative association between personal performance-avoidance goals and engagement and (b) the positive relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
174
3
16

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(207 citation statements)
references
References 72 publications
(132 reference statements)
14
174
3
16
Order By: Relevance
“…While our study failed to find supporting evidence for Grant and Dweck's (2003) proposal regarding multiple types of performance goals, the rest of the results are highly consistent with the existing literature. This study raises the possibility that salient characteristics of the learning environment might negate potentially important distinctions between achievement goals, including their valence (e.g., see Lau & Nie, 2008). We suggest that future research test whether the extremely high correlations among the performance goal components observed in the present study represent generalizable findings across heavily performance-oriented learning environments or culture-specific idiosyncrasies.…”
Section: Mastery and Performance Goals As Conduits Between Contexts Amentioning
confidence: 90%
See 2 more Smart Citations
“…While our study failed to find supporting evidence for Grant and Dweck's (2003) proposal regarding multiple types of performance goals, the rest of the results are highly consistent with the existing literature. This study raises the possibility that salient characteristics of the learning environment might negate potentially important distinctions between achievement goals, including their valence (e.g., see Lau & Nie, 2008). We suggest that future research test whether the extremely high correlations among the performance goal components observed in the present study represent generalizable findings across heavily performance-oriented learning environments or culture-specific idiosyncrasies.…”
Section: Mastery and Performance Goals As Conduits Between Contexts Amentioning
confidence: 90%
“…These perceptions also predict positive affect, greater effort and persistence, less help-seeking avoidance, and deeper cognitive engagement (Ames & Archer, 1988;Karabenick, 2004;Lau & Nie, 2008;Ryan, Gheen, & Midgley, 1998). On the basis of these findings, we hypothesized that perceptions of mastery goal structures in school would predict students' personal mastery goals as well as performance-approach goals focusing on nonnormative positive outcomes.…”
Section: Perceived Social-psychological Contexts On Achievement Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting question for this study is if it is related to classroom goal structure, either directly or indirectly, through students' achievement goals. In a large scale study of fifth grade students in Singapore Lau and Nie (2008) found that a performance goal structure in mathematics classrooms positively predicted effort withdrawal and avoiding challenges in mathematics whereas a mastery goal structure negatively predicted these responses. A possible interpretation of these results is that a performance goal structure in mathematics classrooms increases mathematics anxiety among students.…”
Section: Mathematics Anxietymentioning
confidence: 99%
“…Murayama and Elliot (2009) proposed a framework to assess the connections between CAF, AG and achievement results which included three models (direct effect, indirect effect and interaction effect). The direct effect model considers that the CAF influences the more relevant achievement results, even more than the personal AG (Ames & Archer, 1988;Gutman, 2006;Karabenick, 2004;Lau & Nie, 2008;Nolen, 2003;Turner et al, 2002;Urdan, Midgley, & Anderman, 1998;Wolters, 2004). The indirect effect model hypothesizes that the CAF influences indirectly the more relevant achievement results via its impact on the adoption of personal AG.…”
Section: Introductionmentioning
confidence: 99%